2012
DOI: 10.3354/meps09386
|View full text |Cite
|
Sign up to set email alerts
|

Eelgrass restoration by seed maintains genetic diversity: case study from a coastal bay system

Abstract: Genetic diversity is positively associated with plant fitness, stability, and the provision of ecosystem services. Preserving genetic diversity is therefore considered an important component of ecosystem restoration as well as a measure of its success. We examined the genetic diversity of restored Zostera marina meadows in a coastal bay system along the USA mid-Atlantic coast using microsatellite markers to compare donor and recipient meadows. We show that donor meadows in Chesapeake Bay have high genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 49 publications
3
57
1
Order By: Relevance
“…Many of the Zostera marina populations in southern Chesapeake Bay were decimated by the wasting disease of the 1930s (Orth & Moore 1984) but recovered naturally and have a high genetic diversity (Table 1, Reynolds et al 2012). This is probably due to an abundance of seed from the more northern parts of Chesapeake Bay.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many of the Zostera marina populations in southern Chesapeake Bay were decimated by the wasting disease of the 1930s (Orth & Moore 1984) but recovered naturally and have a high genetic diversity (Table 1, Reynolds et al 2012). This is probably due to an abundance of seed from the more northern parts of Chesapeake Bay.…”
Section: Discussionmentioning
confidence: 98%
“…Recovery in this region is recent (< 15 years), and the young meadows present in this region are either a result of large-scale restoration or natural recruitment. Naturally recruited, restored and source meadows for restoration were included in this survey as well as the previously hypothesized source of natural recruitment (Chincoteague Bay; Harwell & Orth 2002;Reynolds et al 2012) and other representative meadows both north and south of the region. See Table 1 for a summary of sampling sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new transplant technique incorporating seeds has been shown to be very promising in Chesapeake Bay, VA Orth and McGlathery, 2012;Reynolds et al, 2012a). In theoretical terms, the result is not surprisinout linkage disequilibrium.…”
Section: Sources and Type Of Donor Materialsmentioning
confidence: 99%
“…They also identify the depth limit (1.6 m) for eelgrass populations in the coastal bays. Using microsatellite markers, Reynolds et al (2012) show that the high genetic diversity in donor beds from Chesapeake Bay is maintained in meadows restored by seeding in the Virginia coastal bays. found that nitrogen fixation increased as the meadows aged, with older beds fixing almost 3 times more nitrogen than younger meadows and 30 times more than bare sediment.…”
Section: Contributions To This Theme Sectionmentioning
confidence: 99%